Faces of Joblessness Characterising Employment Barriers to Inform Policy - Fernandez, Rodrigo (OECD Social, Employment and Migration Working Papers, 2016)
This paper proposes a novel method for identifying and visualising key employment obstacles that may prevent individuals from participating fully in the labour market. The approach is intended to complement existing sources of information that governments use when designing and implementing activation and employment-support policies. In particular, it aims to provide individual and household perspectives on employment problems, which may be missed when relying on common labour-force statistics or on administrative data, but which are relevant for targeting and tailoring support programmes and related policy interventions. A first step describes a series of employment-barrier indicators at the micro level, comprising three domains: work-related capabilities, financial incentives and employment opportunities. For each domain, a selected set of concrete employment barriers are quantified using the EU-SILC multi-purpose household survey. In a second step, a statistical clustering method (latent class analysis), is used to establish profiles and patterns of employment barriers among individuals with no or weak labour-market attachment. A detailed illustration for two countries (Estonia and Spain) shows that "short-hand" groupings that are often highlighted in the policy debate, such as "youth" or "older workers", are in fact composed of multiple distinct sub-groups that face very different combinations of employment barriers and likely require different policy approaches. Results also indicate that individuals typically face two or more simultaneous employment obstacles suggesting that addressing one barrier at a time may not have the intended effect on employment levels. From a policy perspective, the results support calls for carefully sequencing activation and employment support measures, and for coordinating them across policy domains and institutions